Research on Quantification and Design Evaluation of Visual Perception Beauty of Purple Clay Teapot - Hao Dong; Rong Han; Hong Zhang (E3S Web of Conferences, 2020)
Yixing purple clay teapot is a famous product due to the evolution of tea culture, which has been continued to this day and gradually become a system of cultural hybridity. It is because of its profound cultural and historical accumulation that it has achieved its position in pottery. With the continuous improvement in technology and the accumulation of experience of generations of purple clay artisans, the patterns of the purple clay pots they make are also in a great variety of fantasies. This paper will explore the design aesthetic basis of purple clay teapot from two directions of the visual angle of purple clay teapot, namely the modelling of purple clay teapot and its decoration.